Talent Management : A Literature Review - Hamsal, Hamsal; Saputra, Dian; Zulhelmy, Zulhelmy; Sundari, Eva; Dianto, Iyoyo; Alsukri, Alsukri (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The volume of literature in popular media and among practitioners serves as a guide for practitioners in human resource management, particularly in Talent Management within the business context. However, what constitutes Talent Management and its foundations in the scientific principles of human resources and management? In this writing, we address these questions by examining the issues with the definition of Talent Management and the lack of data supporting many practitioner claims. Subsequently, we outline research that supports a definition of Talent Management as a system-oriented approach focused on strategic talent management. We then delineate future research directions to further develop the field of Talent Management and align it more closely with the extensive body of work in strategic human resource management.